(untitled) (Global Journal of Management and Business Research, 2017)
The purpose of our paper is to analyze the behavior of banks in terms of capital and risk in front of the prudential capital regulation constraints. Our study is based on a panel of Tunisian banks over the period 1996-2014. The findings show that the capital adequacy requirements affect significantly and negatively the capital and positively the risk which adjust simultaneously.